Gyms Customer Loyalty Using the Logistic Regression Algorithm Technique - Munoz, Joaquin Moreno (2022)
The objective of this work is to implement the logistic regression technique in datasets of gyms to identify and make a respective analysis for a correct segmentation of clients and, in this way, maximize the possibility of retaining clients; this will also allow us to rule out wrong decisions and incorrect assumptions, in addition to optimizing management according to customer data, which will be vital for a correct loyalty of gym users. The precision calculated the loyalty by the logistic regression algorithm considering important factors such as the rate of abandonment.